2017
DOI: 10.1128/iai.00140-17
|View full text |Cite
|
Sign up to set email alerts
|

The PerR-Regulated P 1B-4 -Type ATPase (PmtA) Acts as a Ferrous Iron Efflux Pump in Streptococcus pyogenes

Abstract: Streptococcus pyogenes (group A Streptococcus [GAS]) is an obligate human pathogen responsible for a broad spectrum of human disease. GAS has a requirement for metal homeostasis within the human host and, as such, tightly modulates metal uptake and efflux during infection. Metal acquisition systems are required to combat metal sequestration by the host, while metal efflux systems are essential to protect against metal overload poisoning. Here, we investigated the function of PmtA (PerRregulated metal transport… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
30
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(32 citation statements)
references
References 56 publications
2
30
0
Order By: Relevance
“…Two recent studies have confirmed the primary role of PmtA as an Fe 2+ -efflux pump 38, 39 . PmtA is important for resistance to iron intoxication, and a pmtA null mutant accumulates elevated levels of intracellular iron.…”
Section: P-type Atpasesmentioning
confidence: 88%
See 2 more Smart Citations
“…Two recent studies have confirmed the primary role of PmtA as an Fe 2+ -efflux pump 38, 39 . PmtA is important for resistance to iron intoxication, and a pmtA null mutant accumulates elevated levels of intracellular iron.…”
Section: P-type Atpasesmentioning
confidence: 88%
“…The P 1B4 -type ATPases were originally assigned a role in Co 2+ export, based on the properties of some of the first characterized members 53 . However, P 1B4 -type ATPases have recently been found to function instead, or in addition, as Fe 2+ efflux transporters including Bacillus subtilis PfeT 36 , Listeria monocytogenes FrvA 27 , Mycobacterium tuberculosis CtpD 37 , and group A Streptococcus PmtA 38, 39 .…”
Section: P-type Atpasesmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal homeostasis plays a central role in oxidative stress resistance in Gram-positive bacteria (4,44,47,48). In addition to PerR, streptococci also employ MntR, a metalloregulator protein, to control cellular manganese and iron homeostasis (11,16,21,25). Oxidative inactivation of PerR and MntR derepresses the expression of the metal homeostasis-related genes dpr and mntABC (Table 3) (25).…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, bacteria have evolved complex systems to maintain metal homeostasis, such as efflux or sequestration of metals [6]. Moreover, there is mounting evidence that metal homeostasis, maintained via metal efflux pumps, plays a critical role in bacterial physiology and pathogenesis [5][6][7][8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%